A simple and fast algorithm to estimate effective anisotropy parameters - Prajapati, S. (EAGE Publishing BV, 2014)
Anisotropy caused by fine layering is often the differences between velocities achieved by sonic logs and seismic experiments. Due to prominent behavior of anisotropy the identification of potential intervals of reservoir quality sand is a great challenge with substantial evidence of occurrence of transversely isotropic (TI) anisotropy in the subsurface associated primarily with shale. To resolve above issues, we implement the modified and extended Backus's averaging algorithm to estimate the effective stiffness parameters and anisotropic parameters, which is very consistent with the well logs and successfully distinguished potential reservoir embedded by shale.